Re-establishment of the Position of the Second Secretary of the Central Committee of the Communist Party in the Baltic States in the Mid-fifties of the 20th Century - Grybkauskas, Saulius (Genocidas ir rezistencija, 2013)
The re-establishment of the position of the second secretary of the Central Committee of the Communist Party in the Baltic States during Nikita Khrushchev’s rule is at the centre of this article. The predecessors of this important position for control of the republics were the representative of the Central Committee of All-Union Communist Party (the Bolsheviks) (AUCP[B] CC) and of the Council of Ministers of the USSR and subsequently the representative of the institution of the (AUCP[B] CC) bureau for the republic. The article examines the reasons and motives behind Moscow’s 1956 decision to re-establish the practice abolished by Lavrentiy Beria in 1953 of appointing functionaries sent by the Kremlin as second secretaries of the Central Committee of the Communist Party of the Soviet Republics. Before re-establishing the position of second secretary, Moscow took several tactical steps. First, in 1955, it specified a problem in the Baltic States, the lack of development in agriculture, and then organised campaigns and checks and also sent ‘assistance’ teams to the Baltic States, as a result of which the elite of the republics were finally forced to ask the centre to “strengthen the leadership” by sending a second secretary and other functionaries. In December 1955, the resolution ‘On measures to raise agriculture of the Lithuanian SSR’ was adopted, and under its guise in 1956 the position of the second secretary was re-established.